Elucidation of the underlying mechanism of Hua-ban decoction in alleviating acute lung injury by an integrative approach of network pharmacology and experimental verification. (April 2023) - Zhou, Wei; Hu, Zhuannan; Wu, Xianwei; Zhang, Shunxian; Jiang, Yuwei; Tian, Li; Huang, Xing; Ma, Zifeng; Qiu, Lei; Zheng, Peiyong; Zhang, Shaoyan; Lu, Zhenhui
Abstract: The pathogenic hyper-inflammatory response has been regarded as the major cause of the severity and death related to acute lung injury (ALI). Hua-ban decoction (HBD) is a classical prescription in traditional Chinese medicine (TCM). It has been extensively used to treat inflammatory diseases; however, its bioactive components and therapeutic mechanisms remain unclear. Here, we established a lipopolysaccharide (LPS)-induced ALI model that presents a hyperinflammatory process to explore the pharmaco-dynamic effect and underlying molecular mechanism of HBD on ALI. In vivo, we confirmed that in LPS-induced ALI mice, HBD improved pulmonary injury by via down-regulating the expression of proinflammatory cytokines, including IL-6, TNF-α, and macrophage infiltration, as well as macrophage M1 polarization. Moreover, in vitro experiments in LPS-stimulated macrophages demonstrated that the potential bioactive compounds of HBD inhibited the secretion of IL-6 and TNF-α. Mechanically, the data revealed that HBD treatment of LPS-induced ALI acted via NF-κB pathway, which regulated macrophage M1 polarization. Additionally, two major HBD compounds, i.e., quercetin and kaempferol, showed a high binding affinity with p65 and IkBα. In conclusion, the data obtained in this study demonstrated the therapeutic effects of HBD, which indicates the possibility for the development of HBD as a potential treatment for ALI. Highlights: HBD improved the lung injury, either by prophylactic or therapeutic administration in LPS-induced ALI mouse model. HBD acted via NF-κB pathway by an integrative approach of network pharmacology and Western Blot analysis. Two major HBD compounds, i.e., quercetin and kaempferol, showed a high binding affinity with p65 and IkBα, and inhibited the secretion of IL-6 and TNF-α.